Business applications of microcomputers and information technology - Flynn, Meredith (South-Western Educational Pub., 1998)
Provides coverage of information technology, telecommunication, and document- centered processing to illustrate how these topics are changing the way computers are used. Current topics such as multimedia, networking, graphical user interfaces, virtual reality, operating systems, and computer security are covered thoroughly. Each chapter contains a chapter outline, learning objectives, and an introduction to provide a framework to helps students anticipate and focus on chapter content.